PENENTUAN KATEGORI DESAIN SEISMIK PADA STRUKTUR BETON BERTULANG GEDUNG APARTEMEN DELAPAN LANTAI - Santana, Fagan Resha; Budi, Gatot Setya; Yusuf, M. (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2025)
Structural design of buildings must consider earthquake resistance in accordance with the provisions of SNI 1726:2019. This study presents the seismic design category (SDC) planning for a reinforced concrete structure of an eight-story apartment building located in Kubu Raya Regency. The determination process of the seismic design category was carried out by identifying the design earthquake acceleration parameters based on the Indonesian seismic hazard map, calculating the spectral response acceleration factors, and determining the building risk category. The analysis results indicate that the eight-story apartment building falls into Seismic Design Category C, in which the permissible seismic-force-resisting systems are the Intermediate Moment Resisting Frame (IMRF) and the Special Moment Resisting Frame (SMRF). This finding implies that the structure must be designed using a system capable of withstanding moderate to strong earthquake loads while ensuring adequate ductility. The selected category also affects the choice of moment-resisting frame system, reinforcement detailing, and the overall evaluation of structural performance. Therefore, the SDC planning results serve as an essential foundation in designing a building structure that is safe, reliable, and compliant with earthquake resistance standards in Indonesia.